Sound effect of transmitting specific emotions in music performance based on the acoustic properties of conjugated materials - Li, Yangjingyi; Lee, Fenghsu (Frontiers in Chemistry, 2023)
Traditional materials cannot accurately express specific emotions through means such as pone, pitch, and timbre in music performance, making it difficult to adjust sound effects based on specific emotions. This article studied the effects of conjugated materials on timbre, frequency response, and other aspects to achieve better sound effects that convey specific emotions. This article analyzed the acoustic characteristics of conjugated materials and applied them to the sound effect of conveying specific emotions in music performance. Conjugated materials can provide a wider range of tone, pitch, and timbre choices. Performers can choose appropriate tones, pitches, and timbres from conjugated materials to express emotions based on specific emotional requirements, or adjust and transform tones, pitches, and timbres for specific emotions, thereby triggering resonance and emotional resonance within the audience, enabling specific emotions to be more accurately and strongly conveyed to the audience. Compared to in poor soundproofing environments, the average sound absorption coefficient of metal materials in better soundproofing rooms increased by 6.5%, and the average sound absorption coefficient of conjugated materials increased by 25.4%. The average sound absorption coefficient of conjugated materials increased by much more than the average sound absorption coefficient of metal materials. The results of this article emphasized that studying the sound effects of music performance based on the acoustic properties of conjugated materials would help explore and develop more immersive and emotionally rich music experiences.